Relacionamentos sociais de fêmeas de muriquis-do-norte (Brachyteles hypoxanthus, Primates-Atelidae) - Possamai, Carla de Borba (2013)
Most species of mammals live in social groups and form close relationships with their conspecifics. In primates, social groups may vary in their degree of cohesion and in their composition, which is determined by patterns of dispersal. Living in groups provides primates with a social context within which each individual makes decisions that affect its survival and reproductive success, and the stability of these groups depends on the ability of individuals to recognize and remember with whom they have interacted. However, the cues that primates use to recognize one another are still only partially understood. Humans for example rely on faces for important information on the identity, sex, age and intentions of their conspecifics, and there is evidence that at least some non-human primates process information of the faces of conspecifics in similar way. Many primates show a wide variation in coat and skin color and it is believed that these are conspicuous signals directed to their conspecifics as a means of visual communication and individual recognition. The ability to recognize kin, in particular, may be important because cooperation and preferential associations with related individuals are known to bring more direct and indirect benefits in many primates. Typically social relationships of the philopatric members of a group are stronger than those of the sex that disperses. However mechanisms such as familiarity and phenotypic matching may assist in the process of individual recognition among members of the dispersing sex as well. The northern muriquis (Brachyteles hypoxanthus), the subjects of this study, undergo developmental changes in their distinct facial markings that may facilitate their ability to recognize one another from their facial markings, and thus affect their social relationships. Their social relations are egalitarian, and, similar to chimpanzees and spider monkeys, females are responsible for dispersing from their natal groups. However, whether females develop and maintain social relationships preferencially with familiar females (who may also be maternal or paternal sisters) from their natal group after dispersing is not yet known. In this study we aimed to answer three questions related to kin recognition and female social preferences: (i) do maternally related individuals have similar facial features; (ii) are humans able to recognize facial similarities in northern muriquis monkeys that are close maternal kin; and (iii) do northern muriquis maintain preferential associations and affiliative relationships with familiar individuals, which also likely to be maternal or paternal kin, after they leave their natal groups? To answer the first two questions we used photographs of faces of the northern muriquis. Using R program to extract the information contained in the photographs we found that facial pigmentation patterns were similar among close maternal kin. Then we evaluated in a comparative perspective the ability of humans to detect facial similarities in the muriquis. Results from tests involving N=401 volunteers corroborated our prediction that humans identified maternally related northern muriquis on the basis of similarities in their facial features. Finally, we evaluated the social relationships of adult females in three of the four groups that make up the population of the northern muriquis at the RPPN-Feliciano Miguel Abdala, in Caratinga, Minas Gerais, using behavioral data collected from January to December 2011. As predicted, adult females associated with one another more frequently than with other age-sex classes, and focal females associated preferentially with females known from their natal groups compared to unfamilar females, independent of maternal kinship. Our findings indicate that familiarity plays an important role in the post-dispersal social relationships of female northern muriquis, and suggest that northern muriquis use facial recognition to distinguish familiar individuals that may be close maternal, as well as paternal, kin. This study contributes to a growing literature on the mechanisms by which primates recognize one another and the roles of both kinship and familiarity in structuring their social relationships